O instituto da repercussão geral no recurso extraordinário - Dall’Acqua, Thaís Ghelfi (2010)
The present work aims to discuss the General Repercussion institute, established by the Constitutional Reform of 2004 (Constitutional Amendment nº. 45/2004). For the analysis of the topic, first of all, it is necessary to study the general aspects of the extraordinary appeal, and the crisis through which passes the Brasilian Supreme Court, the decisive reason for the institution of the general repercussion as a requirement of access to that Court. To understand the General Repercussion institute will be also analyzed similar institutes, like the extinct “arguição de relevância”, and others institutes originated from the foreign law. From then it will be defined the vague concept and the legal status of the general repercussion. After that, will be discussed the procedimental’s aspects of the institute from the legislation and the Brasilian Supreme Court’s decisions. Finally, this study will be concluded with an examination of the intertemporal law applicable to the institute